Developing Demand Forecasting for Upgrade Projects of Maritime Fire Protection Systems - Kalliovaara, Clarissa (My University, 2022)
Forecasting and planning have gained significant attention from practitioners and academics in the past decades as organizations attempt to navigate their operations in a dynamic business environment. Demand forecasting helps to anticipate probable futures and responding to the continuously emerging rapid changes in demand. Sales and Operations Planning is a process that aids organizations to tackle the different challenges related to forecasting by balancing supply capabilities and customer demand. A modification of the model where inventory management is also considered is SIOP or Sales, Inventory and Operations Planning. SIOP is a dynamic process cycle where operational plans are reviewed and updated on a monthly basis to match supply with the changing demand by bringing together perspectives from different departments. This thesis is a case study with the goal to develop demand forecasting of aftersales services in project business. The case company manufactures fire protection systems and offers aftersales services to them. This study focuses on upgrade projects that are done to the installed systems in marine vessels to increase the systems’ longevity or reliability, for instance. Even though the execution of these projects has been successful, the case company has faced several different challenges with meeting customer demand and the related material requirements of the projects. The case company has adopted the SIOP process for other types of projects, but upgrade projects are not yet included in the cycle. Therefore, this thesis aims to link upgrade projects to the ongoing SIOP process by recognizing the key characteristics and challenges affecting the demand of upgrade projects. This study was conducted through 12 semi-structured interviews within the case company. The interviewees all participate in the upgrade project process, but in different ways. The participants were divided based on if their viewpoints represented the perspective of the factory or the business unit. This helped to gain a comprehensive view of the entire process and what information should be shared to ensure smoother operations. The results indicated that the benefit of the SIOP process and demand forecasting have been recognized in the case company. The key barriers to implementing a forecasting process were insufficient time because of other work and insufficient resources. This hectic nature of the project business has resulted in a lack of proactivity even though its advantages have been recognized. The main challenges affecting upgrade projects were related to scheduling, delivery, planning, and data or information. To improve the demand forecasting process of upgrade projects, a more collaborative approach is required to ensure a more comprehensive understanding of supply capabilities and demand requirements. Including upgrade projects to the SIOP process would allow for better coordination between operations, and fluctuations in demand could be addressed quicker. In addition, utilizing installed base information was recognized to be useful in both demand forecasting and improving proactive sales. Two types of demand were distinguished: a more standard, steady demand and an erratic, lumpy demand. Each of them has different requirements which should be fulfilled.
Keywords: Demand forecasting, sales and operations planning, installed base, project business, aftersales services